GE_GERICHTE P/6051/2024 vom 18. Juli 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;DÉNONCIATION CALOMNIEUSE;ACTE PRÉPARATOIRE(DROIT PÉNAL);ASSASSINAT | CP.303; CP.260bis.al1.letb; CPP.310